The effect of the mu-opioid receptor agonist DAMGO on neonatal rat astrocyte signalling and morphology - O'Brien-Cairney, Jack (2019)
Astrocytes are known for modulating neuronal signalling in a plethora of different ways including the modulation of nociceptive signalling in the central nervous system. In recent years, work has been done to understand how astrocytic signalling is affected by different stimuli which would be released during pain responses. The focus of this study was to observe whether mu-opioid receptor activation had any impact on the magnitude of calcium responses, the number of calcium spikes, or the percentage response rate of astrocytes that had been treated with either 1µM ATP or 100nM SP; and whether mu-opioid receptor activation had any effect on forskolin-induced stellation of astrocytes. Astrocytes were cultured from sacrificed P2 Wistar rats and were loaded with a calcium indicator dye called Fluo-5F AM. The changes in fluorescence intensity expressed by the astrocytes following stimulation with 1uM ATP or 100nM substance P (SP) in the absence and presence of DAMGO ([D-Ala2, N-MePhe4, Gly-ol]-enkephalin) were measured and compared against each other. Cortical astrocytes were incubated both under control conditions and with 10µM DAMGO in the presence and absence of 100µM forskolin for three hours at 37°C prior to being fixed using a 4% PFA solution. The prevalence of stellate morphology was manually assessed and compared using both Kruskal-Wallis and Mann-Whitney statistical tests. The results of this study show that DAMGO reduces the magnitude of calcium responses (from 2.51-fold to 1.36-fold higher than baseline; p<0.0001) and response rate (from 84.62% to 44.60%; p<0.0001) of ATP-treated spinal astrocytes. However, these changes are not found among ATP-treated cortical astrocytes. Similarly, DAMGO appears to have no significant effect on the magnitude or number of calcium responses produced by SP binding among both spinal and cortical astrocytes. However, secondary applications of SP alone significantly reduced calcium response magnitudes among spinal astrocytes (from 2.48-fold to 1.26-fold higher than baseline; p = 0.0009). These results suggest that initial binding of SP causes astrocytes to become desensitised to further SP-induced calcium activity. Chronic (3h) exposure of cortical astrocytes to DAMGO at 37°C and at 5% CO2 had no significant effect on the prevalence of stellate cells compared to those fixed under control conditions (p>0.99). Chronic exposure to a single application of DAMGO and forskolin also did not significantly change the prevalence of stellate cells among those that were treated with solely forksolin for three hours (p>0.99). These results suggest that chronic exposure to a single application of DAMGO has no significant impact on astrocyte morphology.